Higher Education EFL Learners’ Online Self-regulated Learning during the Covid-19 Pandemic: Relationships of Some Variables with Self-regulation - Doğan, Yunus (Children Research Center, 2022)
The sudden implementation of a fully-online education has caught learners in many countries flat-footed, bringing about more responsibilities for self-regulated learning. However, self-regulation seems to be an outstanding challenge facing learner-readiness, satisfaction and achievement in online education during the pandemic period. Nowadays, higher education students fail at effectively self-regulating their online learning experience. Therefore, it is worth identifying whether the situation in this sense has deteriorated or ameliorated during the pandemic process. Thus, this study aimed to understand to what extent higher education students self-regulated their online learning, and what kind of a relationship their self-regulation had with such variables as academic achievement, gender, preferred online learning environment, and attitudes towards the online course (English in this instance). The study also aimed to conduct the validity and reliability analyses of the Turkish version of the scale Self-Regulated Online Learning Questionnaire (SOL-Q). The findings of the study provide educational policy-makers with critical insights into the current situation of fully online education practices in higher education. © 2022 Children Research Center. All Rights Reserved.
İngilizceyi Yabancı Dil olarak Öğrenen Üniversite Öğrencilerinin Covid-19 Sürecinde Çevrimiçi Öz-Düzenlemeli Öğrenme Becerileri: Bazı Değişkenlerle Öz-Düzenleme arasındaki İlişkiler
Keywords: Covid-19; higher education; language learning; online learning; Self-regulated learning